Solve for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> from both sides of the equation.

Divide each term in <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mi>y</mi><mo>=</mo><mn>4</mn><mo>-</mo><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> and simplify.

Divide each term in <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mi>y</mi><mo>=</mo><mn>4</mn><mo>-</mo><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Simplify each term.

Divide <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Dividing two negative values results in a positive value.

Rewrite in slope-intercept form.

The slope-intercept form is <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> , where <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> is the slope and <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> is the y-intercept.

Reorder <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math> .

Reorder terms.

Use the slope-intercept form to find the slope and y-intercept.

Find the values of <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> using the form <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> .

The slope of the line is the value of <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> , and the y-intercept is the value of <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> .

Slope: <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math>

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mn>2</mn><mo>)</mo></mrow></mstyle></math>

Slope: <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math>

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mn>2</mn><mo>)</mo></mrow></mstyle></math>

Any line can be graphed using two points. Select two <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> values, and plug them into the equation to find the corresponding <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> values.

Write in <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> form.

Reorder <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math> .

Reorder terms.

Create a table of the <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> values.

Graph the line using the slope and the y-intercept, or the points.

Slope: <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math>

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mn>2</mn><mo>)</mo></mrow></mstyle></math>

Solve for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> from both sides of the equation.

Divide each term in <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mi>y</mi><mo>=</mo><mn>6</mn><mo>-</mo><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> and simplify.

Divide each term in <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mi>y</mi><mo>=</mo><mn>6</mn><mo>-</mo><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Simplify each term.

Divide <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Dividing two negative values results in a positive value.

Rewrite in slope-intercept form.

The slope-intercept form is <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> , where <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> is the slope and <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> is the y-intercept.

Reorder <math><mstyle displaystyle="true"><mo>-</mo><mn>3</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math> .

Reorder terms.

Use the slope-intercept form to find the slope and y-intercept.

Find the values of <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> using the form <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> .

The slope of the line is the value of <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> , and the y-intercept is the value of <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> .

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mn>3</mn><mo>)</mo></mrow></mstyle></math>

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mn>3</mn><mo>)</mo></mrow></mstyle></math>

Any line can be graphed using two points. Select two <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> values, and plug them into the equation to find the corresponding <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> values.

Write in <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> form.

Reorder <math><mstyle displaystyle="true"><mo>-</mo><mn>3</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mi>x</mi></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math> .

Reorder terms.

Create a table of the <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> values.

Graph the line using the slope and the y-intercept, or the points.

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mn>3</mn><mo>)</mo></mrow></mstyle></math>

Plot each graph on the same coordinate system.

Do you know how to Graph x-2y=4 x-2y=6? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.